1999
DOI: 10.1161/01.atv.19.12.2826
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Genetic Architecture of Lipids, Lipoproteins, and Apolipoproteins

Abstract: Abstract-We review the ways in which twin studies have been used to investigate the genetic architecture of lipids, lipoproteins, and apolipoproteins. We focus on the age dependency of genetic effects and the importance of pleiotropy for the lipid system. Finally, consequences are discussed of age dependency and pleiotropy for the design and power of twin studies aimed at detecting the actual quantitative trait loci (QTLs) involved. It is concluded that twin studies have played an important role and will remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
68
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 94 publications
13
68
1
Order By: Relevance
“…Previous studies indicated existence of age-dependent gene expression in some lipids during adulthood and adolescence Nance et al, 1998;Snieder et al, 1997Snieder et al, , 1999. Our previous studies (Middelberg et al, 2005, 2006), which examined younger (< 30 years old) and older (> 30 years old) adult groups, showed that covariation in lipid levels across time is largely influenced by additive genetic factors and effects of unique environment are largely specific to the different occasions.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies indicated existence of age-dependent gene expression in some lipids during adulthood and adolescence Nance et al, 1998;Snieder et al, 1997Snieder et al, , 1999. Our previous studies (Middelberg et al, 2005, 2006), which examined younger (< 30 years old) and older (> 30 years old) adult groups, showed that covariation in lipid levels across time is largely influenced by additive genetic factors and effects of unique environment are largely specific to the different occasions.…”
Section: Discussionmentioning
confidence: 81%
“…No evidence was found indicating that lipids are influenced by different genes before and after menopause. A recent review of twin studies of lipids and (apo)lipoproteins 11 showed that most studies report h 2 estimates between 40% and 80% for total cholesterol, LDL, HDL, and triglycerides. Estimates of h 2 for apoA1 and apoB were roughly within the same range as for lipid levels.…”
Section: Discussionmentioning
confidence: 99%
“…11 Only one study, which reported on HDL alone, focused on the effect of menopause and found that postmenopausal monozygotic (MZ) twins were more similar (rϭ0.79) than premenopausal MZ twins (rϭ0.61), whereas dizygotic (DZ) similarity did not change (rϭ0. 31 and rϭ0.32, respectively).…”
mentioning
confidence: 99%
“…Heritabilities of lipids have been estimated between 50% and 80% for total cholesterol, LDL, HDL and triglycerides, but twin and family studies have almost exclusively involved Caucasians (Snieder et al, 1999). As a consequence relatively little is known about potential ethnic differences in genetic and environmental influences on lipids.…”
Section: Twin Research and Human Genetics Volume 8 Number 5 Pp 492-498mentioning
confidence: 99%